Upaya Peningkatan Pengetahuan Siswa SMK/SMA Mengenai Kosmetik yang Aman dengan Metode Daring - Djamilah Arifiyana; Vika Ayu Devianti (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
The rise of media coverage regarding the production of illegal and dangerous cosmetics is one proof that the use of cosmetics is currently a necessity. Online marketing is one of the facilities for spreading these illegal cosmetics. Thus, it is necessary to educate the public, especially social media users who are generally in productive age range, to be more careful in choosing safe cosmetics. In this community service activity, education was carried out to 17 participants from senior high school student. The method used includes the presentation by the presenter as well as discussion and question and answer. To measure the increase in knowledge, pre-test and post-test were carried out. It was found that 64.7% experienced an increase in knowledge after this activity was held.